Проблеми формування тестів з курсу фізики у вищій школі - Горіна, Олена (Видавництво Львівської політехніки, 2012)
Рассмотрены преимущества и недостатки тестирования знаний студентов в высшей школе и проблемы, связанные с формированием тестов. Представлена практика разработки тестов на кафедре физики Национального университета “Львовская политехника”. The article considers advantages and disadvantages of testing students’ knowledge in a higher school and the problems associated with the formation of tests. The author submitted the practice of tests formation at the Department of Physics in National University of “Lviv Polytechnics”.
Проблемы формирования тестов по курсу физики в высшей школе
Problems of formation of tests in physics at a high school
Keywords: тест; высшая школа; студент; валидность теста; test; higher school; student; test validity